The Portuguese language assessment in Enem tests: A critical analysis of the instruments of (dis) insertion of the subject in the process of construction of teaching / learning (Research, Society and Development, 2020)
It is evident in our society that the learning assessment practices that have been developed in our educational institutions have not always been used as subsidies that help, improve and exponentiate the teaching and learning processes, as they primarily intend to measure and quantify the knowledge, neglecting the identification and stimulation of certain individual and collective potentials. In this perspective, this work intends to point out intrinsic relationships and problematizations about the evaluation process in High School, highlighting the importance of using the tools to improve teaching practice and in favoring educational policies that respond to the results expressed year after year, emphasizing that the intentionality of the assessment must always be in line with the basic guidelines and the multiple skills that are expected to be improved in each teaching segment, in addition to highlighting the important role of Enem in the systematization of a didactic that excels in the integral development of the expected skills in the Reference Matrix and other official documents that legitimize teaching in Brazil. The study also addresses issues pertinent to the changes that occurred over the years in the Enem assessment mechanisms, for better understanding, we conducted a descriptive and qualitative research, anchored in the studies of (Bakhtin, 1997; Antunes and Luckesi, 2003; Esteban, 2005) , in addition to other authors, who also warn about evaluative issues related to the teaching of Portuguese. In addition, for a better understanding of the lines of this study, we analyzed three questions from the Portuguese language exam of Enem - 2017 based on skills 01 and 09 of the Enem Reference Matrix in order to explain this association between the concept of evaluation and the way in which we understand its applications in Portuguese language teaching practices.